Special Issue “Salmonella: Pathogenesis and Host Restriction” - France Daigle (Microorganisms, 2021)
Bacteria of the Salmonella genus include several serovars that are closely related, although they can colonize different ecological niches, different hosts, and cause different diseases [...]